Analisa Faktor – Faktor Yang Mempengaruhi Gen– Z Dalam Menentukan Keputusan Investasi - Agus Putra Mardika; I Putu Dharmawan Suryagita Susila Putra; Ni Luh Laksmi Rahmantari; Ni Komang Mela Tri Utari; I Gusti Ayu Lia Yasmita (Faculty of Economics and Business, Universitas Warmadewa, 2025)
This study explores the factors that influence investment decisions among Generation Z in Indonesia.Through a qualitative approach, data was obtained from literature review, observation, and in-depthinterviews with 10 Generation Z respondents aged 21-27. This research utilizes the Self-DeterminationTheory (SDT) framework that includes aspects of personal motivation, social influence, self-confidence,independence, social relationships, and external factors. The research findings reveal that Generation Z'sinvestment decisions are driven by the motivation to achieve financial stability, overcome future-relatedconcerns, and recommendations from friends and family. Social media and influencers play an importantrole in shaping their investment preferences. The level of confidence in investing is influenced by theeducation provided by investment platforms and individual experience. While independence is a keyaspect, community input is still considered important. External factors, such as platform promotions andeconomic information, also have a significant influence on investment decisions.The study concludes thatGeneration Z integrates social influences and personal preferences in the investment decision-makingprocess, with a focus on autonomy and achieving long-term financial goals.